Contact inhibition controls cell survival and proliferation via YAP/TAZ-autophagy axis - Pavel, Mariana; Renna, Maurizio; Park, So Jung; Menzies, Fiona M.; Ricketts, Thomas; Fullgrabe, Jens; Ashkenazi, Avraham; Frake, Rebecca A.; Lombarte, Alejandro Carnicer; Bento, Carla F.; Franze, Kristian; Rubinsztein, David C. (Nature Communications, 2018)
Contact inhibition enables noncancerous cells to cease proliferation and growth when they contact each other. This characteristic is lost when cells undergo malignant transformation, leading to uncontrolled proliferation and solid tumor formation. Here we report that autophagy is compromised in contact-inhibited cells in 2D or 3D-soft extracellular matrix cultures. In such cells, YAP/TAZ fail to co-transcriptionally regulate the expression of myosin-II genes, resulting in the loss of F-actin stress fibers, which impairs autophagosome formation. The decreased proliferation resulting from contact inhibition is partly autophagy-dependent, as is their increased sensitivity to hypoxia and glucose starvation. These findings define how mechanically repressed YAP/TAZ activity impacts autophagy to contribute to core phenotypes resulting from high cell confluence that are lost in various cancers.
CRIS-Team Scopus Importer:2020-08-12